How methane yield, crucial parameters and microbial communities respond to the stimulating effect of antibiotics during high solid anaerobic digestion. (July 2019) - Zhi, Suli; Li, Qian; Yang, Fengxia; Yang, Zengjun; Zhang, Keqiang
Graphical abstract: Highlights: The stimulating effect of antibiotics was stronger under low inoculation ratios. Modified Gompertz model fit best for HSAD under different inoculation ratios. Day 5 was the key time point for the stimulating effect occurring. Methanosarcina growth was key reason for the stimulating effect of antibiotics . Abstract: To comprehensively understand how antibiotics affect anaerobic digestion, their stimulating effects on methane production cannot be ignored; however, few studies have evaluated these effects. This study investigated the stimulating effects of three typical antibiotics (oxytetracycline, sulfadimethoxine, and norfloxacin) on high solid anaerobic digestion. The results showed that 100 mg/L antibiotics exhibited a strong stimulating effect on CH4 yield; while other external carbon sources had no obvious effects. The stimulating effect was more obvious under low inoculation ratios, which could improve the system processing capacity of feed sludge. Lower lag phases were given by the modified Gompertz model when stimulating effects occurred. The variations of physicochemical parameters and microbial Venn maps both showed that day 5 was a critical point for digestion time. The relative abundance of Methanosarcina was enhanced when the stimulating effect occurred, whereas Methanoculleus decreased. Different microbial characteristics were obtained for different samples from the heat maps.